Upaya Pusat Pelaporan Dan Analisis Transaksi Keuangan (PPATK) Dalam Mencegah Tindak Pidana Pencucian Uang Dalam Sistem Perbankan - Kalalo, Arce; Darmayanti Putong, Diana (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
The Indonesian Financial Transaction Reports and Analysis Center (INTRAC) is an independent institution under the President which was established with Law No. 8 of 2010 concerning the Crime of Money Laundering. Function of INTRAC are as follows: prevention of money laundering, data and information management, supervision of the compliance of the reporting parties and analyze or investigation of financial transactions that there are reasonable grounds to suspect are related to the commission of a money laundering offence or other crimes acts as referred to in Article 2 Section (1). From the duties and authorities mandated by the Money Laundering Law, PPATK has at least 5 functions, namely financial intelligence, regulators, coordinators, mediators and assistance in law enforcement.In addition, the Financial Transaction Reports and Analysis Center (INTRAC) as an independent institution, also carries out an investigative function, namely collecting, storing, analyzing and evaluating information on transactions that are suspected and suspected of being money laundering.The Indonesian Financial Transaction Reports and Analysis Center (INTRAC) was established with the authority to implement policies to prevent and eradicate money laundering while establishing an anti-money laundering regime in Indonesia.